Volume 4: Heat Transfer; Electric Power 1983
DOI: 10.1115/83-gt-28
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics for Jet Array Impingement With Initial Crossflow

Abstract: Two-dimensional arrays of circular air jets impinging on a heat transfer surface parallel to the jet orifice plate are considered. The jet flow, after impingement, is constrained to exit in a single direction along the channel formed by the jet orifice plate and the heat transfer surface. In addition to the crossflow which originates from the jets following impingement, an initial crossflow is present which approaches the array through an upstream extension of the channel. The temperature of the initial crossf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The studies of Florschuetz et al [2], included the significance of considering initial crossflow for jet impingement array especially in simulating the impingement cooled mid-chord region of a gas turbine airfoil. A similar study of considering initial crossflow effects has been carried out by Chambers et al [3] in which they showed that the initial crossflow strongly influenced the heat transfer distribution by comparing different mass flux ratios between the crossflow and jet. It is not only the flow parameters but also the geometric configuration that influences the heat transfer performance.…”
Section: Introductionmentioning
confidence: 74%
“…The studies of Florschuetz et al [2], included the significance of considering initial crossflow for jet impingement array especially in simulating the impingement cooled mid-chord region of a gas turbine airfoil. A similar study of considering initial crossflow effects has been carried out by Chambers et al [3] in which they showed that the initial crossflow strongly influenced the heat transfer distribution by comparing different mass flux ratios between the crossflow and jet. It is not only the flow parameters but also the geometric configuration that influences the heat transfer performance.…”
Section: Introductionmentioning
confidence: 74%
“…In an investigation by Florschuetz et al (1984) [9], two dimensional arrays of circular jets impinging on a heat transfer surface parallel to the jet orifice plate were considered. The impinging arrays of jets were forced to leave the test section in a single direction through a channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reasonable diameters of impinging hole will help to improve the effect of heat transfer. In the literature [8][9][10][11][12] which use numerical method to study the Impingement cooling, the results shows that the back jet is destroyed by cross flow and lead to the convective heat transfer is complex. Reducing the impact distance and increasing the Reynolds number can increase the convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%